An introduction to Japanese society - Sugimoto, Yoshio 1939- (Contemporary Japanese society, 1997)
"An Introduction to Japanese Society is a provocative, insightful and accessible book that comprehensively examines contemporary Japanese society. It not only provides a thorough and critical analysis of the dominant view that groupism and homogeneity characterise Japanese society, but highlights Japan's internal variation and social stratification. The book covers a wide range of aspects of Japanese society, with chapters on class, geographical variation, generation, work, education, gender, minorities, popular culture, and the establishment." "Yoshio Sugimoto contests the notion that Japanese society comprises an extremely uniform culture, drawing attention to its subcultural diversity and class competition. In offering a comparison with other countries, the book also explores the idea that subcultural groups may have similar characteristics in different societies. Sugimoto also examines what he calls "friendly authoritarianism" - the force behind the Japanese tendency to remain ostensibly faithful to their particular groups and organizations."--BOOK JACKET.